R.A.C.E mentoring and P-12 educators : practitioners contributing to scholarship - Griffen, Aaron J., 1974- (Emerald Publishing Limited : IAP, Information Age Publishing, Inc., 2021)
"Seldom is the practicing P-12 educator, the P-12 practitioner, considered a scholar. R.A.C.E Mentoring and P-12 Educators: Practitioners Contributing to Scholarship explores the unrecognized and infrequently considered teacher scholar, principal scholar, counselor scholar, librarian scholar - the practitioner scholar who if provided the platform and access can produce a unique and complex narrative and knowledge base to fields of study. This volume extends the current knowledge in educational leadership and research, curriculum and instruction, teaching, social justice, and diversity, equity, and inclusion. R.A.C.E Mentoring and P-12 Educators: Practitioners Contributing to Scholarship presents ways to conceptualize quality in educational research by engaging practitioners, researchers and policy makers in cross-disciplinary partnerships to provide an intentional platform for scholars and researchers in the P-12 school systems and pre-service programs, particularly those with/or seeking an active and emerging research and publishing agenda. This volume is divided into four interrelated sections. Section I focuses on mentoring practitioners as scholars during pre-service and in practice. Chapters in this section promote the use of methods coursework, narrative analysis and culturally relevant pedagogy to enhance practitioner agency and roles as scholars. Section 2 includes Culturally Responsive School Leadership (CRSL) as a way to recognize and address the historical examples and barriers to practitioner social justice activism. These chapters center the school setting and graduate coursework, using practitioner scholarship as a way to cultivate critical consciousness and the use of counter-narratives to combat racism, settler colonialism, and classism among school staff. Section III engages practitioner scholarship as a revolutionary approach through case study, auto-ethnography, review of literature, mental models, and phenomenological study. This section fosters the value of practitioner voice as agency to disrupt oppressive ideologies and beliefs that sustain inequitable and unequal school environments. Section IV provides curriculum, instruction, and parent involvement as examples of practitioner advocacy via personal and collective identity development, Black/Crit, Inquiry-Based Learning (IBL) and engagement strategies. These final chapters provide details of policy and practice transformation methods that empower practitioner sustainability of student and parent access to equitable and inclusive school experiences"-- Provided by publisher.
Keywords: Education -- Research -- United States.; Education -- Social aspects -- United States.; Mentoring in education -- United States.; Educational equalization.; Education -- Inclusive Education.; Educational strategies and policy: inclusion.; elektronické knihy; electronic books